2014
DOI: 10.2337/dc13-2804
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor 3 Is Associated With Insulin Resistance and With Incident Type 2 Diabetes Over a 7-Year Follow-up Period: The CODAM Study

Abstract: OBJECTIVEImmune dysregulation can affect insulin resistance (IR) and b-cell function and hence contribute to development of type 2 diabetes mellitus (T2DM). The complement system, as a regulator of immune and inflammatory homeostasis, may be a relevant contributor therein. However, longitudinal studies focusing on complement as a determinant of T2DM and IR are scarce. Therefore, we prospectively investigated the association of plasma complement factor 3 (C3) with (estimates of) IR in muscle, liver, and adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 60 publications
(74 reference statements)
10
58
0
Order By: Relevance
“…A previous study performed in adults showed that low-grade inflammation and insulin resistance might represent two independent pathways by which body fat leads to elevated C3 (27). However, it seems that changes in C3 levels over a 7-year follow-up period were associated with changes in several measures of insulin resistance and that baseline C3 was associated with the 7-year incidence of type 2 diabetes (28). Although the main production of the C3 is in the liver, C3 is also synthesized by activated macrophages (29) and adipocytes (30) as an inflammatory cytokine or an adipokine.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A previous study performed in adults showed that low-grade inflammation and insulin resistance might represent two independent pathways by which body fat leads to elevated C3 (27). However, it seems that changes in C3 levels over a 7-year follow-up period were associated with changes in several measures of insulin resistance and that baseline C3 was associated with the 7-year incidence of type 2 diabetes (28). Although the main production of the C3 is in the liver, C3 is also synthesized by activated macrophages (29) and adipocytes (30) as an inflammatory cytokine or an adipokine.…”
Section: Discussionmentioning
confidence: 81%
“…First, its cross-sectional design, which does not allow drawing conclusions on causality; however, in adults it was observed that C3 was associated with the development of insulin resistance in a longitudinal study (28). Furthermore, the study is limited by the fact that blood samples only reflect inflammation, glucose and insulin concentrations at a given specific time point.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has consistently been associated with a high serum level of C3 in a potentially causal manner [13][14][15][16] . However, the physiological mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We used the gold standard hyperinsulinemic euglycemic clamp technique enabling us to distinguish between hepatic and peripheral insulin resistance. Previous studies have reported associations between high circulating levels of C3 and insulin resistance using the more indirect homeostasis model assessment of insulin resistance (HOMA-IR) [13][14][15][16] . HOMA-IR predominantly reflects hepatic insulin resistance indirectly supporting our results.…”
mentioning
confidence: 99%
See 1 more Smart Citation